Virtual Screening of FDA-Approved Drugs against LasR of Pseudomonas aeruginosa for Antibiofilm Potential - Suhaib Sadiq; Nosheen Fatima Rana; Muhammad Ammar Zahid; Muhammad Kazim Zargaham; Tahreem Tanweer; Amna Batool; Ayesha Naeem; Afrah Nawaz; Rizwan-ur-Rehman; Zahid Muneer; Abdul Rauf Siddiqi (Molecules, 2020)
Pseudomonas aeruginosa is a Gram-negative pathogenic bacterium that is present commonly in soil and water and is responsible for causing septic shock, pneumonia, urinary tract and gastrointestinal infections, etc. The multi-drug resistance (MDR) phenomenon has increased dramatically in past years and is now considered a major threat globally, so there is an urgent need to develop new strategies to overcome drug resistance by P. aeruginosa. In P. aeruginosa, a major factor of drug resistance is associated to the formation of biofilms by the LasR enzyme, which regulates quorum sensing and has been reported as a new therapeutic target for designing novel antibacterial molecules. In this study, virtual screening and molecular docking were performed against the ligand binding domain (LBD) of LasR by employing a pharmacophore hypothesis for the screening of 2373 FDA-approved compounds to filter top-scoring hit compounds. Six inhibitors out of 2373 compounds were found to have binding affinities close to that of known LasR inhibitors. The binding modes of these compounds to the binding site in LasR-LBD were analyzed to identify the key interactions that contribute to the inhibition of LasR activity. Then, 50 ns simulations of top hit compounds were performed to elucidate the stability of their binding conformations with the LasR-LBD. This study, thus concluded that sulfamerazine showed the highest binding affinity for the LasR-LBD binding pocket exhibiting strong inhibitory binding interactions during molecular dynamics (MD) simulation.